Clinical characteristics and outcomes in febrile infants aged 29–90 days with urinary tract infections and cerebrospinal fluid pleocytosis - Moon, Ga Won; Shin, Donghyun; Kim, Young Mi; Choi, Soo-Han (Frontiers in Pediatrics, 2023)
Introduction: Fever without a focus is a common reason for medical evaluations, hospitalizations, and the antimicrobial treatment of infants younger than 90 days. The presence of cerebrospinal fluid (CSF) pleocytosis could be challenge for clinicians who treat febrile young infants with urinary tract infection (UTI). We evaluated the factors associated with sterile CSF pleocytosis and the clinical outcomes of the patients. Methods: A retrospective review of patients aged 29 - 90 days with febrile UTIs who underwent a non-traumatic lumbar puncture (LP) at Pusan National University Hospital from January 2010 to December 2020 was conducted. CSF pleocytosis was defined as white blood cell (WBC) counts ≥ 9/mm3. Results: A total of 156 patients with UTI were eligible for this study. Four (2.6%) had concomitant bacteremia. However, no patients had culture-proven bacterial meningitis. In correlation analysis, although weak strength, CSF WBC counts were positively correlated with C-reactive protein (CRP) level (Spearman r = 0.234; P = 0.003). Thirty-three patients had CSF pleocytosis (21.2%; 95% confidential interval [CI], 15.5 - 28.2). The time from fever onset to the hospital visit, peripheral blood platelet counts, and CRP level at admission were statistically significant in patients with sterile CSF pleocytosis compared to those without CSF pleocytosis. In the multiple logistic regression, only CRP was independently associated with sterile CSF pleocytosis (cutoff, 3.425 mg/dL; adjusted odds ratio, 2.77; 95% CI, 1.19 - 6.88). The proportion of fever defervescence by hospital day 2 was 87.9% in patients with CSF pleocytosis and 89.4% in those without CSF pleocytosis (P = 0.759). There was no statistical difference in the fever defervescence curves between the two patient groups (P = 0.567). No patients had neurological manifestations or complications. Conclusions: Coexisting sterile CSF pleocytosis among febrile infants with UTIs suggest a systemic inflammatory response. However, the clinical outcomes between the two groups were similar. A selective LP should be considered in young infants with evidence of UTI, and inappropriate antibiotic therapy for sterile CSF pleocytosis should be avoided.